Organizational and economic mechanism of management by the enterprise sustainable development subject to production risk - Kovalenko Inna; Sokolytsyn Alexander (Научно-технические ведомости СПбГПУ: Экономические науки, 2019)
The innovative way of development of the Russian economy is focused on the technological development of the domestic production complex, which requires the development of the appropriate mechanisms to ensure sustainable industrial enterprises' economy development. Production activity stabilization is associated with risk management. Since the long-term preservation of competitive advantage in the conditions of the new technological structure depends not only on the traditional resource base but also on the social and human capital development, re-searchers naturally increase their attention to the risks of the enterprise associated with the working conditions and these conditions impact on the production activities economic indicators. The purpose of the study is to develop an organizational-economic mechanism for the sustainable development management of an enterprise based on a production risk assessment. In the article problems are solved : approaches to the definition "sustainable development enterprise" are ana-lysed; the assessment of the industrial injuries impact on the indicators of enterprise sustainability is given; a management system for the enterprise sustainable development has been developed; the organizational and economic mechanism for the sustainable development management of an industrial enterprise has been formulated. As a result, the enterprise sustainable development is defined by the authors as the enterprise passage along a life-cycle curve with a minimum gap between planned and actual characteristics, subject to minimal costs for ensuring such a steady-state. Enterprise sustainability is considered in four aspects: economic, social, environmental, and institutional. The relevant indicators of enterprise sustainability are identified. The components of the damage to the enterprise as a result of industrial injuries are highlighted, the calculation of the total damage is made by the example of an oil refinery. The author's definition of the risk associated with hazardous working conditions and industrial injuries as a production risk is substantiated. A step-by-step system for enterprise sustainable development management taking into account production risk is presented. An organizational-economic mechanism for managing the sustainable development of an enterprise has been developed, with management subject and management object description, goals, objectives, functions, principles, methods, tools, and its implementation main stages. The implementation of the organizational and economic mechanism allows strengthening the company's position in an unstable external environment? in its institutional, economic, social and environmental aspects. The directions of further research are seen in the development of an economic-mathematical model of the automated system for the enterprise sustainable development management based on production risk assessment as a tool for the described organizational and economic mechanism.